2012
DOI: 10.1136/bmjopen-2012-001469
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of a patient decision aid to improve decision quality and glycaemic control in people with diabetes making treatment choices: a cluster randomised controlled trial (PANDAs) in general practice

Abstract: ObjectiveTo determine the effectiveness of a patient decision aid (PDA) to improve decision quality and glycaemic control in people with diabetes making treatment choices using a cluster randomised controlled trial (RCT).DesignA cluster RCT.Setting49 general practices in UK randomised into intervention (n=25) and control (n=24).ParticipantsGeneral practices Inclusion criteria: >4 medical partners; list size >7000; and a diabetes register with >1% of practice population. 191 practices assessed for eligibility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
159
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(162 citation statements)
references
References 33 publications
0
159
0
3
Order By: Relevance
“…The reduction in decisional conflict after completion of the FADA was expected and supports the hypothesis that people who use a decision aid are more likely to make an informed and value-based decision, and as a result, they are more likely to persist with their decision (de Achaval et al, 2012) and may have better outcomes (Mathers et al, 2012). However, others have argued that the decisional conflict can encourage appropriate deliberation and enhance doctor-patient relationship (O'Connor, 1995b, O'Connor, 1995a, Nelson et al, 2007a, Nelson et al, 2007b).…”
Section: Discussionmentioning
confidence: 61%
“…The reduction in decisional conflict after completion of the FADA was expected and supports the hypothesis that people who use a decision aid are more likely to make an informed and value-based decision, and as a result, they are more likely to persist with their decision (de Achaval et al, 2012) and may have better outcomes (Mathers et al, 2012). However, others have argued that the decisional conflict can encourage appropriate deliberation and enhance doctor-patient relationship (O'Connor, 1995b, O'Connor, 1995a, Nelson et al, 2007a, Nelson et al, 2007b).…”
Section: Discussionmentioning
confidence: 61%
“…Luego de realizar una búsqueda sistemática de la literatura, encontramos seis ECA que evaluaron HATD en pacientes con diabetes mellitus [22][23][24][25][26][27] (Tabla 1). En general, estos estudios confirmaron los resultados de la revisión Cochrane.…”
Section: El Desafío Es La Situaciónunclassified
“…The participants also felt more engaged in their diabetes management despite the lack of clinical outcomes. Similarly, Mathers et al, 111 in a RCT of a decision aid for patients with type 2 diabetes (adults aged between 42 and 87 years), found no statistical effect on glycaemic control (HbA 1c decreased in both intervention and control groups), but decision-making by patients was more autonomous and promoted more realistic expectations and greater knowledge. The authors suggested that this can lead to better long-term SM practices.…”
Section: Shared Decision-makingmentioning
confidence: 99%
“…Both of these studies involved the use of a decision aid in a single consultation between a clinician and a person with diabetes. In the Mathers et al 111 study, the mean duration of the consultation was 15.31 minutes. People living with dementia and diabetes are likely to need interventions that involve more frequent contact and include repetition and reinforcement.…”
Section: Shared Decision-makingmentioning
confidence: 99%